The effect of mouth rinses on surface micro hardness of two esthetic restorative materials - kanan, Sabiha; mohammed, Amaal (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To evaluate the effect of mouth rinses (Biofresh and ZAK) on the surface micro hardnessof two light cure restorative material (Tetric ceram ivoclar-vivadent) and (3M Z 250) dentalcomposite.Methodology: The microhardness values of (sixty) composite specimens were measured at the topsurfaces after 24 hours of immersion in different solutions (Biofresh, Zak mouth wash and distilledwater as control). Comparison done using descriptive statistics (mean, SD, SEM, minimum andmaximum values) and inferential statistics (ANOVA and LSD) test.Results: The biofresh mouth rinse which has high alcohol containing has less effect onmicrohardness of tetric ceram than the zak &distiled water , while the effect of Zak mouth rinse onmicrohhybrid composit (3M Z250) is less than biofresh &distiled water, also there was highlysignificant difference between subgroup of tetric ceram and the same for (3M Z250) composite & theeffect of the mouth rinse on hardness was material dependent it may be attributed to the differencesin chemical composition and filler type of each material. Since it was found that alcohol is not the onlyfactor that has the softening effect on the restorative material, other ingredient in a mouth rinse. mayhave softening effect on polymer matrix.Recommendations: We recommend for a comparison of color stability for restorative materialunder the effect of mouth rinsing.